Impact Assessment of Smartfarm Program Laznas Indonesian Zakat Initiative (IZI) in Improving the Welfare of Mustahik - Karyanto, Karyanto; Setiadi, Iwan (PARADIGMA : JURNAL ILMU PENGETAHUAN AGAMA, DAN BUDAYA, 2025)
The study was conducted to see the impact of the smartfarm program on improving the welfare of mustahik using qualitative methods of conducting interviews and quantitative methods of administering questionnaires to respondents randomly to measure how much mustahik practices agricultural knowledge in the agricultural business activities carried out and improving the welfare of mustahik on an economic scale, and to measure how much support Laznas Inistiatif Zakat Indonesia and the government have. The results of the study showed that mustahik in practicing agricultural knowledge and skills obtained from Smartfarm program training in their agricultural businesses were 16% to 55%, and still <85% of the success indicator value. The improvement in the welfare of mustahik experienced an economic increase of 12% to 38% and was still <60% of the program's success indicator value. Improvements need to be made by Laznas Inisiatif Zakat Indonesia in achieving the success indicators (1). The preparation of training materials is adjusted to the age level, education level, agricultural experience, and business plans that will be pursued, (2). Increasing the selling value of hygienic and attractive agricultural products for the target of middle to upper class consumers and the role of other family members by processing agricultural products into food and drinks that have high selling value (3). Support from the government, zakat collection institutions and the private sector in the development of modern agriculture in the smartfarm program so that food security for the community, especially in the Tangerang Regency area.